GA, in a Word - Gans, Eric Lawrence (2022)
Ἐν ἀρχῇ ἦν ὁ λόγος, καὶ ὁ λόγος ἦν πρὸς τὸν θεόν, καὶ θεὸς ἦν ὁ λόγος. In the beginning was the Word, and the Word was with God, and the Word was God Why is it not absurd to claim that John 1:1’s claim that the (human) world originated with the Logos, best understood...